Within and Beyond the Nucleotide Addition Cycle of Viral RNA-dependent RNA Polymerases - Gong, Peng (Frontiers in Molecular Biosciences, 2022)
Nucleotide addition cycle (NAC) is a fundamental process utilized by nucleic acid polymerases when carrying out nucleic acid biosynthesis. An induced-fit mechanism is usually taken by these polymerases upon NTP/dNTP substrate binding, leading to active site closure and formation of a phosphodiester bond. In viral RNA-dependent RNA polymerases, the post-chemistry translocation is stringently controlled by a structurally conserved motif, resulting in asymmetric movement of the template-product duplex. This perspective focuses on viral RdRP NAC and related mechanisms that have not been structurally clarified to date. Firstly, RdRP movement along the template strand in the absence of catalytic events may be relevant to catalytic complex dissociation or proofreading. Secondly, pyrophosphate or non-cognate NTP-mediated cleavage of the product strand 3′-nucleotide can also play a role in reactivating paused or arrested catalytic complexes. Furthermore, non-cognate NTP substrates, including NTP analog inhibitors, can not only alter NAC when being misincorporated, but also impact on subsequent NACs. Complications and challenges related to these topics are also discussed.